Micro-stories, Robotic Coding, Digital Applications, and Augmented Reality to Enhance Children's Computational Thinking [Microrrelatos, codificación robótica, aplicaciones digitales y realidad aumentada para potenciar el pensamiento computacional infantil] - M. Esther Del-Moral-Pérez; Nerea López Bouzas; Jonathan Castañeda-Fernández (Pixel-Bit)
This research evaluates the potential of an educational intervention aimed at developing Computational Thinking (CT) in preschool students aged 4 to 6 years (N=82). The proposal is a playful approach based on a story featuring a robot, which students must code to navigate a physical scenario and overcome various challenges by interacting with digital applications and Augmented Reality (AR). The study follows a pre-experimental design with a descriptive and comparative methodology, using a pre-test/post-test to assess CT levels based on key skills: algorithmic thinking, generalization, abstraction, decomposition, and evaluation. The results highlight the effectiveness of the proposal in enhancing CT in most students, regardless of gender and age. Students with Special Educational Needs and Disabilities (SEND) also showed an improvement in their CT skills, albeit with greater challenges. All participants were introduced to robotic coding, which contributed to strengthening their spatial orientation, laterality, counting skills, hand-eye coordination, logical reasoning, and more. In conclusion, the use of a playful narrative fostered students' connection with the story and empathy with the characters, enhancing their engagement with the proposed tasks and reducing their complexity.